Utilization Of White-Meat, Red-Meat And Super Red Dragon Fruit (Hylocereus sp) Skin Waste As An Alternative Food Source - Syahputri, Yulian; Widiastuti, Diana (Journal of Science Innovare, 2018)
Dragon fruit skin, waste material (dragon fruit waste), will have a profitable sale value if it can be used as a food raw material. Dragon fruit skin waste contains relatively high dietary fiber so it can be used as a food raw material. This study aims to utilize dragon fruit skin waste for the manufacture of dragon fruit skin flour as an alternative food source. Some tests are made on white-meat dragon fruit skin, red-meat dragon fruit skin and super red dragon fruit skin. The preliminary study is the soaking of the three types of dragon fruit skin in two solutions, namely 0.1% sodium citrate and 0.1% sodium metabisulfite to prevent the browning effect on flour. Dragon fruit skin flour from the soaking with both solutions is then characterized physically, including its texture, color, flavor and rendement. The best physical characterization is followed by chemical characterization, including the contents of  water,  ash, protein, fat, carbohydrate, dietary fiber, minerals (Fe, Na, K, Ca and P), and also microbiological characterization of Escherichia coli, molds and Bacillus cereus. The chemical and microbiological characterization shows that the red-meat dragon fruit skin flour has better results than the white-meat and super red dragon fruit skin flour does. The red-meat dragon fruit skin flour contains 8.80% water, 0.20% ash, 2.35% fat, 7.69%, protein, 68,29% carbohydrate and 28,72% dietary fiber as well as 4.40 mg K, 8.76 mg Na , 0.65 mg Fe , 10.20 mg Ca and 32.58 mg P. Keywords: Waste, Dragon Fruit Skin, Dragon Fruit Skin Powder, Alternative Food Source